Auschwitz i nowoczesność - Krupa, Bartłomiej (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The text examines the relationship between the two categories – Auschwitz and modernity, in recognition of Jean Améry and Zygmunt Bauman, taking also into account the voice of the latter polemicists. In the first place is reconstructed Améry’s positive view on modernity with respect for the truth of the victims of Auschwitz. Then Bauman's critical position is discussed, indicating the modern provenance of the Holocaust and risk of recurrence of the Holocaust. Next the voices of Bauman’s opponents are presented. Yehuda Bauer, Henryk Grynberg, Andrzej Szahaj and Stefan Morawski pointed to the key role of ideology and irrational aspects of Nazism. At the end the common ground of Améry and Bauman is indicated – both turn to take the perspective of the victims.
Auschwitz and modernity